PENDAMPINGAN HILIRISASI DURIAN MENJADI LEMPOK IMUT SEBAGAI OLEH-OLEH KHAS OKU - Sari, Fifian Permata (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2025)
The aim of this community service activity is to provide assistance to the community in processing durian as a fruit that is widely cultivated and is characteristic of local fruit wealth in South Sumatera, especially in OKU Regency.  So far, when durian is harvested in large quantities, it is only sold fresh or made into tempoyak. The method used in this service activity are observation, persuasive and cognitive method through  a  direct training and practice method for PKK women, Lubuk Raja District, OKU Regency, South Sumatera Province. The results shows that there was an increase in the participants' knowledge, and skills in processing durian into snacks in the form of cute lempok which can be used as a typical OKU souvenir. Assistance and training with direct practice so that people are trained in making durian snacks as souvenir products and it is hoped that this program can continue in the future. It is hoped that the cute lempok innovation will be able to contribute to increasing people income through the sale of new innovative souvenirs.